Cancer survival in Cali, Colombia: A population-based study, 1995-2004 (Colombia Medica, 2014)
Background: There is limited information on population-based cancer survival data in Latin America.Objetive: To obtain estimates of survival for some cancers recognized as a public health priority in Colombia using data from the Cancer Registry of Cali for 1995-2004.Methods: All cancer cases for residents of Cali were included for the following sites: breast (3,984), cervix uteri (2,469), prostate (3,999), stomach (3,442) and lung (2,170).  Five-year relative survival estimates were calculated using the approach described by Estève.Results: Five-year relative survival was 79% in patients with prostate cancer and 68% and 60% in women with breast or cervix uteri cancer, respectively. The cure fraction was 6% in subjects with lung cancer and 15% in those with stomach cancer. The probability of dying from breast or prostate cancer in people in the lower socio-economic strata (SES) was 1.8 and  2.6  times greater,  respectively,  when compared to  upper SES, p